Analisis Daya Tahan Otot Tungkai dan Koordinasi Mata-Kaki Terhadap Kemampuan Sepak Sila Permainan Sepak Takraw pada Mahasiswa Putra Stkip Paris Barantai Kotabaru - Arham Syahban (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
This study aims to analyze of endurance of leg muscles and eye-foot coordination on the sepak sila ability to sepak takraw game for male students of STKIP Paris Baranta Kotabaru. The research method used is quantitative descriptive analysis method with data collection techniques using test techniques and measurements of the strength of endurance of leg muscles and eye-foot coordination as well as their respective contributions to the ability of sepak sila in sepak takraw games. The population of this research is all male students of the Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Paris Barantai. Samples were taken as many as 30 male students using the sampling method, namely simple random sampling. From the results of the study it is known that there is a contribution of endurance of leg muscles (X1) to the ability of sepak sila in the sepak takraw game of STKIP Paris male students Barantai Kotabaru (Y) of 32.3%, known to have eye-foot coordination (X2) to the ability of sepak sila in the sepak takraw STKIP Paris male students Barantai Kotabaru (Y) amounted to 31.7% and it was known the contribution of endurance of limb muscles (X1) and eye-foot coordination (X2) together towards the ability to the ability of sepak sila in sepak takraw games of male students of STKIP Paris Barantai Kotabaru (Y) is 61.1%. Keywords: Leg Muscle Endurance, Eye-foot Coordination, Sepak Sila Ability in Sepak Takraw Games